2018
DOI: 10.1021/acs.biochem.8b00242
|View full text |Cite
|
Sign up to set email alerts
|

Improved Method for the Incorporation of Heme Cofactors into Recombinant Proteins Using Escherichia coli Nissle 1917

Abstract: Recombinant production of heme proteins in Escherichia coli is often limited by the availability of heme in the host. Therefore, several methods, including the reconstitution of heme proteins after production but prior to purification or the HPEX system, conferring the ability to take up external heme have been developed and used in the past. Here we describe the use of the apathogenic E. coli strain Nissle 1917 (EcN) as a suitable host for the recombinant production of heme proteins. EcN has an advantage over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 38 publications
2
35
1
Order By: Relevance
“…We have recently shown that E. coli Nissle (EcN) is a very suitable host for the production of heme proteins [13]. Within the present study, we went a step further and constructed a T7 (Fig.…”
Section: Construction Of the New Ecn(t7) Strainmentioning
confidence: 90%
See 1 more Smart Citation
“…We have recently shown that E. coli Nissle (EcN) is a very suitable host for the production of heme proteins [13]. Within the present study, we went a step further and constructed a T7 (Fig.…”
Section: Construction Of the New Ecn(t7) Strainmentioning
confidence: 90%
“…Therefore, it can be used to successfully saturate proteins with heme cofactor during protein production. In this way, the cofactor is incorporated in a more native coordination than by adding the heme cofactor to the completely folded protein [13]. Unfortunately, the EcN strain lacks the gene for T7 RNA polymerase which is required for the use of T7 promoter-based expression vectors like the widely used pET system or Duet-vectors [14].…”
Section: Introductionmentioning
confidence: 99%
“…While RdmS_sGAF2 displays two distinct peaks in this region, only one peak was detected in the ferrous form of MsmS_sGAF2, suggesting a different heme iron coordination. While the heme in MsmS exists as a mixture of 5c and 6c (Fiege et al, 2018), the heme iron in RdmS_sGAF2 appears to be mainly 6c. Whether this is of functional significance is currently unknown.…”
Section: Rdms Contains a Heme Cofactor In The Second Gaf Domainmentioning
confidence: 99%
“…Expression in EcN was performed as described before (Fiege et al, 2018). For the production of the full-length protein, LB-high salt medium (LB-HS: 10 g/l tryptone, 5 g/l yeast extract, 24.22 g/l NaCl) was used.…”
Section: Recombinant Protein Production In E Coli Nissle 1917 (Ecn)mentioning
confidence: 99%
“…We have recently shown that E. coli Nissle 1917 (EcN) is a very suitable host for the production of heme proteins [14]. In this study, we went a step further and constructed a T7 promoter compatible strain to overcome the limitation of recombinant protein production in EcN to expression vectors lacking the T7 promoter.…”
Section: Construction Of the New Ecn(t7) Strainmentioning
confidence: 99%